Enhancing Language Proficiency through Task-Based Language Teaching: Evidence from EFL Classrooms - Hamroyeva Muborak Jumanazarovna, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article investigates the effectiveness of Task-Based Language Teaching (TBLT) in developing communicative competence among English as a Foreign Language (EFL) learners in secondary school settings. Drawing on established theoretical frameworks and recent empirical classroom research, the study explores how TBLT enhances learners’ speaking fluency, motivation, learner autonomy, and overall communicative ability. Classroom observations, pre- and post-task speaking assessments, and learner feedback were collected over a three-week instructional unit in Uzbekistan. The findings reveal that well-structured, meaningful tasks significantly increase learner engagement, authentic language use, and confidence. Despite contextual challenges such as large classes and exam-driven environments, the study advocates for the integration of TBLT cycles into curriculum design, providing practical strategies for teachers working in resource-constrained settings. Future directions for research and pedagogical implications are discussed.